Tourism-phobia in historic centres: the case of Malaga - Fernando Almeida-García; Rafael Cortés-Macías; Antonia Balbuena-Vázquez (Boletín de la Asociación de Geógrafos Españoles, 2019)
The annoyance presented by the residents in the historic centre of Malaga, due to the impact of tourism is analysed. The study area is affected by a declining population and problems presented by residents in intense tourism spaces. The existence of tourism-phobia and the elements involved in it are examined. To this end, a specific questionnaire was produced about tourism-phobia, 378 surveys were distributed and completed and 10 semi-structured interviews were carried out with residents. Likewise, a thematic map was created, spatially identifying the main problems relating to the nuisances to residents. This research is the first study that analyses tourism-phobia by using statistically reliable samples. The results show the existence of a group of residents who are quite annoyed (17.5 %) that can be classified as tourism-phobic and a group that is not very annoyed at all (22.2 %) that could be classed as tourism-philic. There are sociodemographic variables that are essential to interpreting these attitudes, such as the cases of the level of education and place of residence. The spatial distribution of the perceptions of the annoyance caused by tourism is uneven in the historic centre of Malaga.